Comparison of anonymous tracker algorithms / Nur Shafikah Mat Daud - Mat Daud, Nur Shafikah (2014)
The Internet has rapidly grown due to more online users using to interact with people, communicate, seek jobs, find partners and shop. Nowadays, Internet become as a basis platform for users by using social networking that can access of any information that need and share interests in lot of ways. The aim of doing this research is to solve problem of anonymous tracker called as virtual communicates. The problem facing on how to track people with anonymous involve matters of legal issues and cyber crime. Based on this research, the objectives to be achieved are to identify IP Address of anonymous tracker, to locate IP Address where anonymous tracker location and comparison of anonymous tracker algorithms. The research metodology consists of several steps consists of gathering information, data collection, data analysis and system development and finally result analysis. The outcomes of the end results of the IP Address are presented. By using the IP Address, can help easily to track location of anonymous. Then, time processing and accuracy which one is the best of algorithms will be determine. The research is provide useful significance that able to detect identity of user allow as anonymous and able to detect location of user through IP Address. In detail section the research create an own website which accessed by users. The website used in this research refer as blog. Here, the users who only access and comment the blog that will allow as anonymous. This research hopes to give significance to solve the problems that occur due by anonymous in social networking.